1997
DOI: 10.1021/jp962943h
|View full text |Cite
|
Sign up to set email alerts
|

Two Methods of Two-Step Excitation Thermal Grating Technique for Detection of Transient Absorption and Stimulated Emission

Abstract: Two different methods for detection of the transient absorption (TA) and stimulated emission (SE) by using a two-step excitation thermal grating technique are characterized. The sensitivity and the temporal profile of the signals are analyzed in detail. One of them, prepulse−(delay)−grating pulse sequence, provides a very sensitive TA detection with a zero background. The other one, grating pulses−(delay)−boosting pulse sequence, has also a very high sensitivity for the detection of TA and SE together with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Recently, Kennis et al 16 reported the direct observation of the photochemical reverse reaction using the transient absorption technique and found that the D state is regenerated on an ultrafast time scale (100 ps) upon photoexcitation of the T state. Using this method combined with a two-step transient grating (TG) method, 17 we measured the refolding dynamics of the linker by initially accumulating the T state by preirradiation with blue light and subsequently photoexciting the T state using a pulsed UV laser (308 nm) to measure the TG signal.…”
mentioning
confidence: 99%
“…Recently, Kennis et al 16 reported the direct observation of the photochemical reverse reaction using the transient absorption technique and found that the D state is regenerated on an ultrafast time scale (100 ps) upon photoexcitation of the T state. Using this method combined with a two-step transient grating (TG) method, 17 we measured the refolding dynamics of the linker by initially accumulating the T state by preirradiation with blue light and subsequently photoexciting the T state using a pulsed UV laser (308 nm) to measure the TG signal.…”
mentioning
confidence: 99%